(untitled) (Equity: Jurnal Ekonomi, 2025)
This study aims to determine the relationship between brand experience and perceived value on customer loyalty through customer satisfaction in buying Warda Skincare products. This research uses a quantitative approach by taking 140 samples from women over 17 years old. Questionnaire data collection methods and studies related to the indicators used. The results of this study indicate that brand experience has a positive and significant effect on customer loyalty. Perceived value has a positive and significant influence on customer loyalty. Brand experience has a positive and significant influence on customer satisfaction. Perceived value has a positive and significant influence on customer satisfaction. Customer satisfaction has a positive and significant influence on customer loyalty. And customer satisfaction is able to mediate brand experience variables and perceived value on customer loyalty.